DESIGN MODELING EXPANSION LOOP OF SUBSEA PIPELINE IN MADURA OFFSHORE USING THE FINITE ELEMENT METHOD - Hafizh Izzatullah, Muhammad
Excessive thermal expansion will cause the pipe to bend and burst. According to Berliner (1974), the expansion that occurs in the pipe can be restrained by introducing an expansion loop as a node on the pipe. In this final project, an analysis was conducted on a pipe equipped with an expansion loop to address the high. The expansion loop was modeled with various sizes using the finite element method to examine the impact of stress and displacement on the pipe. Before the expansion loop analysis was performed, the pipe was also designed to ensure the structural strength and stability of the subsea pipe. The pipe wall thickness was designed based on the standards of DNV ST F101, API RP 1111, and ASME B31.8 to ensure the pipe can withstand hoop stress. The concrete coating thickness was designed based on the DNV RP F109 standard to ensure pipe stability. From the design process, a pipe wall thickness of 12.7 mm (0.5 inches) and a concrete coating thickness of 40 mm without trenching were obtained. Used size for modeling expansion loop with size W an H ratio of 12:6 was determined. According to the modeling results of several expansion loop variations using ABAQUS software, it was found that for the L21 shape with a size of (6:12), the stress and displacement values were 401.2 MPa and 4.68 meters, respectively; for the L22 shape with a size of (12:6), the stress and displacement values were 403.1 MPa and 4.27 meters, respectively; for the U11 shape with a size of (12:6:12), the stress and displacement values were 402.75 MPa and 4.21 meters, respectively; for the U12 shape with a size of (6:6:6), the stress and displacement values were 401.8MPa and 4.24 meters, respectively; for the U13 shape with a size of (12:12:12), the stress and displacement values were 400.7 MPa and 5.47 meters, respectively; for the Z31 shape with a size of (12:6:12), the stress and displacement values were 402.3 MPa and 4.72 meters, respectively; and for the Z32 shape with a size of (6:6:6), the stress and displacement values were 395 MPa and 5.49 meters, respectively. Therefore, the stress does not exceed 90% of SMYS, so using an expansion loop makes the pipe safer.